The Effect of Cash Turnover and Customer Growth on Profitability at PT Bank BRI Branch Unit Sawang Lhokseumawe - Yusuf, Zulfan; Rizal, Syamsul (Indonesian Journal Economic Review (IJER), 2022)
This study aims to determine the extent of the influence of cash turnover and growth in the number of customers on profitability at PT. Bank BRI (Persero) Lhokseumawe branch, Sawang Cash Office, North Aceh. Based on the results of the study illustrates that the increase in cash turnover and the number of customers contributed to increasing the profitability of PT. Bank BRI (Persero) Lhokseumawe branch office, Sawang unit, North Aceh Regency. With high cash flow turnover, banks can channel the proceeds from revolving funds to other productive sectors quickly and accurately, of course with a fluctuating profit level. Thus PT. Bank BRI (Persero) Lhokseumawe branch office, Sawang cash office have contributed to increased economic growth in Aceh in general, North Aceh, in this case Sawang District, North Aceh Regency in particular. This can be seen from the growth of various products and community businesses as well as the use of natural resources as superior products from Sawang District, North Aceh Regency.